Improving Bank Customers’ Satisfaction through Relationship Marketing Practices - Okonkwo, Chinwendu Deborah; Ugwuonah, Geraldine (International Journal of Marketing Research Innovation, 2019)
In recent times, since the cost of retaining an existing customer has been confirmed to exceed that of acquiring new ones, the emphasis has been on retaining existing customers. This study examines how bank customers’ satisfaction could be improved through some specific relationship marketing practices. This study focused on three banks within Enugu metropolis in Nigeria. The descriptive research design was adopted.384 self-administered, structured questionnaires were distributed, out of which 332 copies were returned. Data was presented using frequencies and cross tabulations. One-sample t-test and Analysis of Variance were used to test hypotheses. Findings revealed that there is a significant relationship between banks’ current relationship strategies and the level of bank customers’ satisfaction; and that bank customers are not highly satisfied with their banks’ relationship with them. Thus, customers’ satisfaction could further be improved if the banks applied some specific relationship marketing practices such as ensuring that customers’ needs are adequately met, and their complaints tackled promptly. The study recommended that these banks could go beyond the conventional practice of outward show of appreciation of customer patronage, but rather work towards resolving customers’ complaints, and meeting their needs promptly.